Epidemiology of Pneumococcal Carriage among HIV-Infected Individuals in the Conjugate Vaccine Era: A Study in Southern Ghana. (13th February 2019) - Dayie, Nicholas TKD; Baffuor-Asare, Michael; Labi, Appiah-Korang; Obeng-Nkrumah, Noah; Olayemi, Edeghonghon; Lartey, Margaret; Slotved, Hans-Christian; Donkor, Eric S.
Abstract : Carriage of pneumococcus is considered as the precursor for development of pneumococcal disease. In sub-Saharan Africa, very little research has been done on the pneumococcus in relation to people with HIV infection in the era of pneumococcal conjugate vaccines. This study investigated pneumococcal carriage among HIV/AIDS patients in southern Ghana to determine the prevalence, risk factors, serotypes and antibiotic resistance of the organism. This was a cross sectional study involving 245 HIV/AIDS patients recruited from Korle Bu Teaching Hospital and Princess Marie Louis Hospital in Accra from November 2016 to March 2017. Epidemiological data on demographic, household and clinical features of the study participants were collected. Nasopharyngeal (NP) swabs were also collected from the study participants and cultured for Streptococcus pneumoniae ; the isolates were serotyped by latex agglutination and Quellung reaction. Antimicrobial disc susceptibility was performed on the isolates, and antibiotics tested included tetracycline, erythromycin, cotrimoxazole, levofloxacin, oxacillin and ceftriaxone. Prevalence of pneumococcal carriage among the study participants was 11% (95% CI: 7.4 to 15.6); carriage among children and adults was 25% (95% CI: 14% to 38.9%) and 7.3% (95% CI: 4% to 11.9%) respectively. School attendance (p=0.001) and history of pneumococcal disease in the past year (p=0.001) were significantly associated with pneumococcal carriage. The most prevalent pneumococcal serotypes carried by the study participants were 19A (15.4%) and 23F (15.4%). Serotype coverage of the various pneumococcal vaccines were PCV10 (23.1%), PCV13 (42.3%) and PPV23 (50%). The prevalence of pneumococcal multidrug resistance was 18.5%. In conclusion, pneumococcal carriage among HIV-infected children was three-fold higher compared to carriage among HIV-infected adults. Pneumococcal carriage among both HIV-infected children and adults in the study area tends to be characterized by a predominance of non-vaccine serotypes and a considerable level of multidrug resistance.